(untitled) (La Rivada, 2025)
This essay explores the ontological relationships between humans and non-humans in Bañado de los Pantanos (La Rioja, Argentina), through ethnographic work carried out with two local women: María Quintero and Dionisia González. Their practices with the loom and the carob tree reveal how objects, beings, and landscapes interact in everyday life, sustaining memory, subsistence, and cultural identity. From an ontological perspective, these practices are analyzed as forms of resistance and knowledge transmission that link art, ritual, and economy in a community context.